The role of opioid peptides in regulation of bile secretion in intact and isolated liver - I. V. Roudin; M. A. Medvedev (Бюллетень сибирской медицины)
Influence of dalargin (non-selective mand d-аgonist), DADLE (selective) and DAGO (selective magonist) on the bile secretion frequency and cholates secretion was studied in acute experiments on isolated perfused liver of the white rats. Opioid peptides effects on isolated liver were revealed to mask by the higher levels of hierarchic regulation in intact liver.